Manejo del discurso en medios de comunicación digitales sobre la situación de los migrantes venezolanos en la ciudad de Latacunga. - Pruna Toro, Esteban Rodrigo (2023)
This research investigates the way in which the digital media of Latacunga address the issue of migration in the city, specifically in the case of Venezuelan citizens. The theoretical analysis reflects on digital journalism, the structure, content and the processes of creation and dissemination of information in digital media, the discourses in which the issue of migration appears in digital media and more specifically migration in Latacunga and your online media. To develop the field work, given the nature of the subject and the approach, the qualitative methodology was used; Two interviews were conducted with representatives of the digital communication media, as well as interviews with authorized voices both on the subject of digital journalism and on the subject of migration.